Total Endovascular Treatment of Aortic Arch Disease Using an Arch Endograft With 3 Inner Branches. (August 2017) - Spear, Rafaëlle; Clough, Rachel E.; Fabre, Dominique; Roeder, Blayne; Hertault, Adrien; Martin Gonzalez, Teresa; Azzaoui, Richard; Sobocinski, Jonathan; Haulon, Stéphan
Purpose: To report early experience with a new endovascular graft developed for aortic arch aneurysm repair in patients unfit for open surgery.Case Report: Three consecutive men (62, 74, and 69 years old) at high risk for open repair were treated for postdissection aortic arch aneurysms using a custom-made 3 inner branched endovascular graft. The 2 proximal branches are antegrade and perfuse the innominate artery and the left common carotid artery; the third branch is retrograde and perfuses the left subclavian artery. The latter is preloaded with a catheter and wire to aid cannulation. Technical success was achieved in each case. The mean procedure time, fluoroscopy duration, and contrast volume were 180 minutes, 35 minutes, and 145 mL, respectively. The perioperative period was uneventful. All branches were patent on 6-month computed tomography and duplex ultrasound imaging.Conclusion: This new patient-specific device allows total endovascular revascularization of the supra-aortic trunks during arch repair. These encouraging results support its more widespread use.